Numerical study ofthe mechanical behaviour of railway wheels containing tearing on the tread. - BOUSSALIA, L.; BELLAOUAR, A. (Science des matériaux (Laboratoire LARHYSS); Vol. 8 No 01 (2017): Science des matériaux (Laboratoire LARHYSS) Moi de Janvier, 2017)
ABSTRACT With the intention of ensuring security and diminishing the costs of service in the railway systems, it is necessary to characterize the mechanical behavior of the zone containing tearing of metal caused by a manufacturing defect which can be at the origin of breaks. The influence of these defects, present in the metal of the wheel was studied by simulating three geometrical forms: circular defect, elliptical defect and any form defect. The constraints and distortions were analyzed in the immediate neighborhood of these defects. The Calculations were performed for a level of load corresponding to the weight of the trailer of the new railcars in Algeria and to the assistant of a code of calculation by finished elements (ANSYS).